CHANGES IN THE LANDSCAPES OF THE FOOTHILLS AS A RESULT OF ANTHROPOGENIC IMPACT - Alimdjanov Nozimjon Nimadjanovich,; Naimov Husniddin Nuriddin ugli, (PEDAGOGS, 2025)
Foothill landscapes, transitional zones between lowland plains and mountainous regions,  are  characterized  by  diverse  ecosystems,  rich  biodiversity,  and  unique geomorphological features. These areas are often subject to significant anthropogenic impacts due to their accessibility and resource availability. Human activities such as agriculture,  urbanization,  deforestation,  and  infrastructure  development  have profoundly altered these landscapes, leading to changes in soil composition, vegetation cover, and hydrological systems. This article examines the extent and nature of these changes,  focusing  on  the  ecological  and  geomorphological  consequences  of anthropogenic  activities  in  foothill  regions.  The  study  aims  to  analyze  the  primary drivers  of  landscape  transformation,  assess  their  impacts,  and  discuss  potential mitigation strategies.